Syarat Cukup Ketaksamaan Hӧlder dan Ketaksamaan Minkowski di Perumuman Ruang Morrey - Ummah, Nahdliyatul; Rahman, Hairur; Ismiarti, Dewi (Jurnal Riset Mahasiswa Matematika, 2022)
The purpose of this research is to show the sufficient condition for Hӧlder inequality and Minkowski inequality in generalization of Morrey space and its weak space, namely generalization of weak Morrey space. This research focuses on the application of Hӧlder inequality and Minkowski inequality in generalization of Morrey space and generalization of weak Morrey space based on the characteristics of the two spaces in the set of n-dimensional real numbers.